Velocity : the seven new laws for a world gone digital. - Ahmad, Ajaz, ....-; Olander, Stefan, ....- (London : Vermilion, 2012)
How can you win when the only certainty is change? Highly accessible, lively and inspiring, Velocity draws upon the authors' unique perspectives and experiences to present seven timeless new laws for businesses and individuals in a world that is dominated by rapid change and digital technology. Written as a fascinating and enjoyable conversation between the authors - Stefan Olander, Vice President of Digital Sport from Nike and Ajaz Ahmed founder and Chairman AKQA - Velocity's up-to-date examples illustrate key lessons, together with insights, ideas and inspiration that individuals and businesses should adopt to thrive. Velocity shares the vision and values required to succeed with the untold backstories to influential and iconic innovation. Fast paced, useful, provocative and highly motivating, Velocity will arm you with actionable ideas to define your future.Features: - 4 Velocity principles: Speed, Direction, Acceleration, Discipline. - 7 Laws, including 'A Smith & Wesson beats four aces', 'It's easier done than said', 'Convenient is the enemy of right' and 'No good joke survives a committee of six'.
Keywords: Recht